Formulation and Pharmaceutical Evaluation of Extemporaneous α-arbutin Creams for the Treatment of Melasma - Veerawat Teeranachaideekul (2022)
Concentrated 7% w/w a-arbutin cream was formulated and evaluated using O/W and W/O emulsion bases as an extemporaneous preparation for melasma treatment. Cream bases were formulated with two pH values, 4.0 and 5.5, using a hot process. The stability of the creams was studied for 60 days under three storage conditions (i.e., 2°C to 8°C, 30°C, 40°C). Cream characteristics and all aspects of product stability including physical, chemical, and microbial were investigated. Stability was defined as no dramatic change in color, viscosity, pH, and no visible microbial growth. For stability, at least 90% of the initial a-arbutin concentration quantified by stability-indicating high-performance liquid chromatography must be obtained. It was found that pH had no influence on the a-arbutin or formulations' stability. All formulations had a-arbutin remaining higher than 90% (approximately 92%) after being stored for 60 days in all storage conditions with no significant changes in pH or viscosity. All samples complied with the microbial limits test for nonsterile pharmaceutical preparation for cutaneous products. However, a color change was detected in O/W and W/O emulsions, especially at 40°C storage condition within 28 and 14 days, respectively. Drug crystals were observed in W/O emulsion stored at 2°C to 8°C. Concerning the in vitro drug release, a-arbutin was released from O/W emulsion but not from W/O emulsion. From the above results, the O/W emulsion that was developed in this study can be used as a cream base for concentrated a-arbutin as an extemporaneous preparation. The developed a-arbutin cream prepared using O/W emulsions can be used as an extemporaneous preparation with a beyond-use date of 60 days when stored at room temperature (30°C) and in the refrigerator (2°C to 8°C).